THE EFFECT OF INSTITUTIONAL IMAGES AND MOTIVATION ON REPURCHASE INTENTION (COLLABORATION INTENTION PARTNERSHIP) THROUGH CUSTOMER SATISFACTION IN UNIVERSITAS BRAWIJAYA - Caecaria, Dhimaz Sectio; Hermawan, Agus; Siswanto, Ely (FIA UB, 2022)
This study aims to examine more deeply how Institutional Images and motivation effected on collaboration intention/Repurchase Intention partnership through customer satisfaction in Universitas Brawijaya. This study uses descriptive explanatory quantitative approach which describes the relationship between variables and a population of 100 partner who repeat their collaboration. The sampling technique used Saturation Sampling which amounts to 100 collaboration partners. The results showed that direct and indirect how institutional images, motivation, and customer satisfaction had a significant influence on repurchase intentions. Eventually in this research found that Institutional images that direct significant influence to Repurchase intention is better than motivation to repurchase intention, and motivation that direct significant influence on customer satisfaction is better than Institutional images to customer satisfaction. Meanwhile in indirect influence is significant effected repurchase intention through customer satisfaction is better with motivation than institution images. This research can be a source of information or reference for policy in Universitas Brawijaya or collaboration partners so that they can continuously maintenance their partnership in mutually benefit if possible.